Innovations and Issues in Monetary Policy: Panel Discussion - Feldstein, Martin; King, Mervyn; Yellen, Janet L. (American Economic Review, 2004)
Martin Feldstein:1 Chairman Alan Greenspan's remarks today give us an opportunity to understand his thinking about monetary policy and about the Federal Reserve's actions during the past 15 years. It was a period of substantial accomplishment that no doubt reflects in considerable measure the views of the Chairman himself. The Fed's primary goal, price stability, has been achieved, with inflation down from 4 percent at the end of the 1980's to about 1.5 percent now. The 2-percentage-point difference between the interest rate on conventional Treasury bonds and on inflation-indexed bonds (TIPS) shows that financial markets expect inflation will remain at about 2 percent for at least the next decade.